2012
DOI: 10.1007/s10792-012-9701-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraocular pressure according to corneal thickness before and after excimer laser corneal ablation for myopia

Abstract: Intraocular pressure is affected by corneal thickness and biomechanics. Following ablative corneal refractive surgery, corneal structural changes occur. The purpose of the study is to determine the relationship between the mean central corneal thickness (CCT) and the change in intraocular pressure measurements following various corneal ablation techniques, using different measurement methods. Two hundred myopic eyes undergoing laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK) were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Insufficient fluorescein use causes false-low readings, and excessive fluorescein use causes false-high readings. The presence of corneal epithelial defects and previous corneal surgeries also complicate measurements 11. Finally, there is a contamination risk, so the tool tip must be cleaned after each use 12…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient fluorescein use causes false-low readings, and excessive fluorescein use causes false-high readings. The presence of corneal epithelial defects and previous corneal surgeries also complicate measurements 11. Finally, there is a contamination risk, so the tool tip must be cleaned after each use 12…”
Section: Discussionmentioning
confidence: 99%
“…31 A significant reduction in keratometry of 5.56 D was also reported (P<0.05). 12 Another study by Zare demonstrated a significant reduction in corneal resistance factor and corneal hysteresis in post PRK eyes when compared with their preoperative baseline. 37 The study also compared the effect of PRK with or without adjunctive mitomycin C on postoperative IOP readings and corneal biomechanical properties, which were measured by Goldmann applanation tonometry and ocular response analyzer.…”
Section: Corneal Biomechanical Properties After Prkmentioning
confidence: 97%
“…11,12,31,36,37,39 Study by Hamed Azzam has demonstrated a significant reduction of mean CCT by 75.5μm in post PRK eyes, when compared with the mean CCT before operation. 12 Munger showed that the measured change in CCT is found to be dependent on the amount of spherical correction during PRK in hyperopic eyes, but not on the cylindrical correction. 31 Six months after PRK, every diopter of applied spherical correction will result in 5.0± 0.9μm of corneal thinning.…”
Section: Corneal Biomechanical Properties After Prkmentioning
confidence: 99%
See 1 more Smart Citation
“…As they mentioned, there are limitations associated with intraocular pressure (IOP) measurements after refractive surgery. [ 1 2 ] Therefore, no acceptable definition is available for steroid-induced ocular hypertension after refractive surgery, and various authors have employed different criteria to ascertain this. For instance, Busool et al classified patients as steroid responders if they had an IOP elevation of at least 25% while on topical steroid treatment (minimum of 28 mmHg) followed by an IOP drop of at least 25% when steroid treatment was discontinued.…”
mentioning
confidence: 99%